Dinamika Kepemimpinan Pesantren NU dan Muhammadiyah dalam Merespons Situasi Krisis - Rahmayanti, Ismi; Suparto, Suparto; Han, Muhamad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2025)
This study examines the dynamics of pesantren leadership in responding to crisis situations using Anthony Giddens' structuration theory. The research focuses on two Islamic boarding schools affiliated with different Islamic organizations: Darul Arqam (Muhammadiyah) and Darus Sunnah (NU). The findings reveal that organizational background significantly shapes leadership responses and decision-making models. NU-affiliated pesantren tend to exercise greater flexibility in interpreting external policies, while Muhammadiyah-based pesantren generally follow formal directives issued by their central board. Nevertheless, both pesantren leaders demonstrate the ability to reflect upon and adapt policies according to the local socio-cultural context. The study highlights how structuration during times of crisis is a dynamic interplay between institutional structures, external authority, and the agency of pesantren leaders in crafting responsive and context-sensitive strategies.